Pencemaran Besi dan Mangan pada Airtanah di Kota Palu, Sulawesi Tengah - Atmaja, Ammar Dwi; Wilopo, Wahyu; Warmada, I Wayan (Universitas Negeri Gorontalo, 2025)
Palu City is one of the major cities on Sulawesi Island, experiencing rapid population and economic growth. However, the 2018 earthquake, tsunami, and liquefaction events caused infrastructure and environmental damage, affecting water resources in the area. Therefore, this study aims to determine the pH, temperature, DHL, TDS, and iron and manganese content of groundwater. The study was conducted by directly measuring the physical and chemical properties of groundwater in 25 water sources, including springs, dug wells, and drilled wells. In addition, groundwater and aquifer material samples were taken for laboratory testing using AAS and XRD. The results of the study showed that the groundwater pH ranged from 7.0 - 8.3, temperature 27.4 oC to 36.1oC, TDS ranged from 170mg/L – 4,733 mg/L, DHL ranged from 341µS/Cm – 9,513µS/Cm, iron content 0.1 – 0.26 mg/L and manganese content 0.16 mg/L – 0.38 mg/L. The source of iron and manganese is indicated to come from the aquifer as shown by the XRD results containing Hematite, Magnetite and Pyrolusite minerals not from anthropogenic activities.